Challenges for Anti-Trafficking NGOs in Indonesia - Iannone, Aniello; Kinasih, Sri Endah; Wahyudi, Irfan (University of Jember, 2024)
NGOs play a crucial role in safeguarding human dignity, especially in developing countries like Indonesia, where they strategically work to address pressing human rights issues. However, NGOs encounter various challenges that impede their efforts. This research specifically focuses on the challenges faced by NGOs working in human trafficking and exploitation in Indonesia. The analysis is based on data obtained from interviews conducted with four NGOs and an independent worker specializing in the exploitation and trafficking of underage individuals. Moreover, this study delves into the socio-economic problems underlying human trafficking in Indonesia. Drawing inspiration from Marxist theories of labor and poverty, it posits that the issue of human trafficking in Indonesia is closely intertwined with socio-economic instability—particularly affecting the most impoverished segment of the population. The research identifies poverty as a key factor fueling exploitation and trafficking in Indonesia. Furthermore, the study reveals implementation challenges and a lack of alignment with international conventions, such as the Palermo Protocols, in enforcing Indonesia's national law against human trafficking (Law No. 21/2007). These issues are particularly apparent in cases involving underage victims. Keywords: exploitation, human trafficking, NGO, Indonesia